Parametric Modeling for Globoidal Cam Based and NC Machining - Guangguo Zhang; Wei Jiang; Lei Zhang; Zhibin Chang; Haitao Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The design and machining of globoidal cam is difficult, because the shape of working surface is complex,and the curved surface of its space is undevelopable. Based on the above reasons,we proposed the parametric Modeling method for globoidal cam based. Through the secondary development, we realized the parameterized modeling of globoidal cam. Base on using of globular indexing cam NC milling machine existing in the lab,research the programming technology,analyses the defects of conventional programming method,raise improvement measures,control the programming error,modify the feeding speed,develop the special purpose programming software, creat globular indexing cam NC machining program automaticly ,improve the machining precision and efficiency of globular indexing cam. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2027